2009
DOI: 10.1007/s00338-009-0483-y
|View full text |Cite
|
Sign up to set email alerts
|

Highly restricted gene flow and deep evolutionary lineages in the giant clam Tridacna maxima

Abstract: The tropical Indo-West Pacific is the biogeographic region with the highest diversity of marine shallow water species, with its centre in the Indo-Malay Archipelago. However, due to its high endemism, the Red Sea is also considered as an important centre of evolution. Currently, not much is known about exchange among the Red Sea, Indian Ocean and West Pacific, as well as connectivity within the Indo-Malay Archipelago, even though such information is important to illuminate ecological and evolutionary processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
103
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 89 publications
19
103
2
1
Order By: Relevance
“…Most of the past research supports the Center of Origin hypothesis (Barber et al 2006, Williams 2007, Timm & Kochzius 2008, Nuryanto & Kochzius 2009). In contrast, relatively few cases substantiate the Center of Overlap (Teske et al 2005, Gaither et al 2011) and Center of Accumulation hypotheses (Wilson et al 2001, Drew & Barber 2009).…”
Section: Origin Of Pomacentrus Coelestismentioning
confidence: 88%
See 1 more Smart Citation
“…Most of the past research supports the Center of Origin hypothesis (Barber et al 2006, Williams 2007, Timm & Kochzius 2008, Nuryanto & Kochzius 2009). In contrast, relatively few cases substantiate the Center of Overlap (Teske et al 2005, Gaither et al 2011) and Center of Accumulation hypotheses (Wilson et al 2001, Drew & Barber 2009).…”
Section: Origin Of Pomacentrus Coelestismentioning
confidence: 88%
“…However, Cende rawasih Bay was the only population har boring extremely low haplotype (0.1538 ± 0.1261) and nucleotide (0.0005 ± 0.0008) diversity, indicating that the population may have suffered a recent bottleneck or founder event (Grant & Bowen 1998). Previous phylogeographic studies of various marine taxa have also found unique genetic diversity in the Cenderawasih Bay region (Barber et al 2006, Crandall et al 2008, Nuryanto & Kochzius 2009. Allen & Erdmann (2006) hypothesized that the bay was essentially isolated for substantial periods over the past 5 million years.…”
Section: Genetic Diversitymentioning
confidence: 94%
“…Menurut Weeden et al (1992), hasil isolasi DNA tersebut masih bisa digunakan sebagai template yang cukup baik untuk reaksi PCR. Kondisi tersebut juga pernah dilaporkan pada beberapa penelitian terdahulu yang memperoleh produk PCR dengan kuantitas dan kualitas yang baik meskipun menggunakan templat DNA berupa DNA smear (Nuryanto & Kochzius, 2009;Nuryanto et al, 2012;Azizah et al, 2015).…”
Section: Hasil Dan Pembahasanunclassified
“…crocea throughout Wallacea using mitochondrial (mtDNA) markers [24][25][26], allozymes [27,28], and microsatellites [29]. Both T. crocea and T. maxima have been shown to contain distinct mtDNA clades associated with Sumatra (Sunda), Wallacea, and northwest New Guinea (Sahul, particularly in Cenderawasih Bay) [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Both T. crocea and T. maxima have been shown to contain distinct mtDNA clades associated with Sumatra (Sunda), Wallacea, and northwest New Guinea (Sahul, particularly in Cenderawasih Bay) [24][25][26]. These lineages are sympatric in some populations, for instance T. maxima from northern Java has both Sumatran and Wallacean mitotypes, and similarly T. crocea populations from Halmahera eastward through Cenderawasih Bay contain both Wallacean and northwest New…”
Section: Discussionmentioning
confidence: 99%